Efektivitas Model Pembelajaran D Efektivitas Model Pembelajaran Discovery Ditinjau dari Kemampuan Komunikasi Mahasiswa Program Studi Pendidikan Matematika STKIP Hermon Timika: - A Rasul; Ruben Sonda (FKIP Universitas Mataram, 2026)
This research is a quasi-experimental study aimed at determining the effectiveness of the discovery learning model in terms of the mathematical communication skills of students. The population of the study consists of all second-semester students, totaling 46 students. The sample of this study includes all second-semester students amounting to 23 students and fourth-semester students also amounting to 23 students selected through purposive sampling techniques. The design used is a pretest-posttest control group design with assessment techniques using test methods. The data collected consists of test scores related to the mathematical communication skills of students. Based on the t-test and proportion test at a significance level of 5%,It was concluded that the discovery learning model is not effective in terms of the mathematical communication skills of students. However, students who participated in discovery learning have higher mathematical communication skills compared to those who underwent conventional learning